2004
DOI: 10.1161/01.hyp.0000144799.41945.a5
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Factor VII Polymorphisms and Blood Pressure

Abstract: Abstract-The purpose this study was to determine whether Arg353Gln and Ϫ323Del/Ins polymorphisms of factor VII (FVII) are related to blood pressure levels and hypertension. Subjects were drawn from the Stanislas Cohort, a longitudinal, familial French cohort examined twice since 1994. The "blood pressure study" included 1342 subjects free of medication use that could affect blood pressure. The "hypertension study" included 645 normotensive and 77 hypertensive adult subjects. Association with hypertension was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
(43 reference statements)
2
10
0
Order By: Relevance
“…Vascular tone, inflammation, blood viscosity, and angiogenesis can play roles in initiating and maintaining an elevation in BP and, therefore, are potential mechanisms contributing to the association between FACTOR VII and risk factors like smoking, diabetes, hypertension, and mental stress. The FVII polymorphisms were reported to be associated with decreased blood pressure and a decreased risk of hypertension [36], suggesting that these FVII variants might influence cardiovascular risk through mechanisms other than thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular tone, inflammation, blood viscosity, and angiogenesis can play roles in initiating and maintaining an elevation in BP and, therefore, are potential mechanisms contributing to the association between FACTOR VII and risk factors like smoking, diabetes, hypertension, and mental stress. The FVII polymorphisms were reported to be associated with decreased blood pressure and a decreased risk of hypertension [36], suggesting that these FVII variants might influence cardiovascular risk through mechanisms other than thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…rs6046G>A in F7 was shown to be associated with increased F7 plasmatic levels [15]. More interestingly, this SNP was reported to have a role in protection against myocardial infarction in two different studies performed on Italian populations [29], [30].…”
Section: Discussionmentioning
confidence: 93%
“…These genetic variants were candidate markers for cardiovascular disease (CVD) risk factors, specifically involved in the predisposition to essential HTN (rs1799752Ins>del in ACE ), in the development of atherosclerotic plaques and in the progression of atherosclerosis ( rs5882A>G in CETP , rs1801133C>T in MTHFR rs662A>G in PON1 and rs1800629G>A in TNF ) [12]. In addition, rs5355C>T in SELE [13], [21], rs1800790G>A in FGB [14], rs6046G>A in F7 [15], rs328C>G in LPL [16], [22] were chose based on our previous published studies that found these SNPs associated with BP levels and/or HTN in European populations [12][16], [21], [22]. Finally, rs3025058T>Ins in MMP3 was selected from an internal investigation showing a link between this genetic variant and BP levels.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation, blood coagulation cascade, cellular adhesion molecules and lipid metabolism all appear to have significant roles [6-8]. While aspects of BP regulation may be the product of an inflammation stimulus [6,9], thrombin is also known to induce several intracellular pathways [7], to modulate vascular tone [7,10] and to have pro-inflammatory effects [7]. Growing evidence also suggests that cellular adhesion molecules and apolipoproteins are closely related to HT [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence also suggests that cellular adhesion molecules and apolipoproteins are closely related to HT [8,11]. All of these factors may be involved in initiating and maintaining elevated BP levels [7]. Overall, however, the genetic factors associated with BP are poorly characterized and the effects of metabolic pathways highlighted by previous studies remain unclear.…”
Section: Introductionmentioning
confidence: 99%